(untitled) (The Peerian Journal, 2024)
The review presents how polymers play their roles in genetic engineering and biotechnological applications, including gene transfer, CRISPR-Cas9-mediated gene editing, vaccine development, and regenerative medicine. To explain how polymers contribute to the improvement of such technologies, various research methods were used, including literature review and case studies.